2019
DOI: 10.1177/1550147719841003
|View full text |Cite
|
Sign up to set email alerts
|

Secret sharing-based authentication and key agreement protocol for machine-type communications

Abstract: One of the main challenges for the development of the Internet of Things is the authentication of large numbers of devices/sensors, commonly served by massive machine-type communications, which jointly with long-term evolution has been considered one of the main foundations for the continued growth of Internet of Things connectivity and an important issue to be treated in the development of 5G networks. This article describes some protocols for the group-based authentication of devices/sensors in Internet of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…• weak/broken or inadequate authentication (e.g., single-factor authentication method using a username and password) [8,23,26,37,38]; • broken access control [23]; • Evolved Packet System Authentication and Key Agreement (EPS-AKA) protocol is vulnerable to several well-known attacks, such as man-in-the-middle (MITM) and denial of service (DoS), and suffers from the disclosure of user identity on first access to the network [39]; • 5G-AKA allows for replay attacks since authentication and synchronization failure messages are sent to the device in plain text [40]; • other messages, such as RRC (Radio Resource Control) and NAS (Non-access stratum), are sent to the device in plain text, which can generate DoS and other attacks that compromise the confidentiality, as already happens with 4G [40]; • lack of attestation to know if a device is compromised [13];…”
Section: Processmentioning
confidence: 99%
See 3 more Smart Citations
“…• weak/broken or inadequate authentication (e.g., single-factor authentication method using a username and password) [8,23,26,37,38]; • broken access control [23]; • Evolved Packet System Authentication and Key Agreement (EPS-AKA) protocol is vulnerable to several well-known attacks, such as man-in-the-middle (MITM) and denial of service (DoS), and suffers from the disclosure of user identity on first access to the network [39]; • 5G-AKA allows for replay attacks since authentication and synchronization failure messages are sent to the device in plain text [40]; • other messages, such as RRC (Radio Resource Control) and NAS (Non-access stratum), are sent to the device in plain text, which can generate DoS and other attacks that compromise the confidentiality, as already happens with 4G [40]; • lack of attestation to know if a device is compromised [13];…”
Section: Processmentioning
confidence: 99%
“…The greater the size, the greater the number of research papers identified. The solutions addressing different threats focused on design, implementation, security analysis, and security assurance frameworks [13,24,32,50,67,[80][81][82][83][84]; systems for security assurance [47], intrusion detection [29] and security incident management [85]; approaches/mechanisms for security [7,25,28,40,41,43,45,48,[86][87][88][89][90][91] and remote diagnostics [92]; schemes for security assurance [72,73,[93][94][95]; protocols for security assurance [8,16,39,53,62,63,[96][97][98][99][100][101]; algorithms for security assurance [102]; models/algorithms for securi...…”
Section: Proposed Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…III. 3GPP NETWORK ARCHITECTURE The physical entities involved in the 3GPP network architecture, as in [18], [19], are sub-grouped into the following 3 domains as mentioned below in Figure 1:…”
Section: Existing Authentication and Key Agreement Protocolsmentioning
confidence: 99%